Developing the global student : higher education in an era of globalization - Killick, David (Milton Park, Abingdon, Oxon ; New York, NY : Routledge, 2015)
"Developing the Global Student addresses the question of how students of higher education can emerge from their university life better equipped to dwell more effectively, ethically, and comfortably amidst the turmoils of a globalising world. It does this from a number of theoretical perspectives, illustrating the nature of the personal and educational challenges facing the individual student and the teaching professional"--
Includes bibliographical references (p. 187-205) and index.
Keywords: Education, Higher; College students; Education and globalization; EDUCATION / Professional Development; EDUCATION / Higher; EDUCATION / General